An Outline of the Geology of Labrador - Greene, B. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1974)
Summary Labrador forms the eastern portion of the Precambrian Canadian Shield. It is divisible into four geologic provinces, each characterized by different orogenic history. Superior Province, in Western Labrador, and Nain Province, along the eastern and northern coast, represent parts of Archean orogenic belts. Both consist primarily of high grade metamorphic rocks, which in Nain Province are overlain locally by less deformed Proterozoic sedimentary and volcanic assemblages. Churchill Province trends northward across central Labrador, between the two older orogens. It is composed of a western belt of relatively little deformed sedimentary and volcanic rocks, and an eastern zone of high grade metamorphic rocks, both of which were last deformed in the Early Proterozoic Hudsonian orogeny. Grenville Province trends east-northeast across sothern Labrador. It is composed largely of quartzo-feldspathic gneisses, last deformed in the Grenvillian orogeny of the Middle Proterozoic. The metamorphic rocks of Grenville, Nain and Churchill Provinces are intruded by large anorthosite-adamellite plutons, emplaced during the Middle Proterozoic. Exploration in Labrador has been concentrated in two areas: the Labrador Trough, in the western part of Churchill Province, and the "Central Mineral Belt" of Labrador, which extends eastward across the southern parts of Churchill and Nain Provinces. Mining in the Labrador portion of the Trough accounts for about half of Canada's iron ore production. Uranium, copper, beryllium and molybdenum occurrences are being investigated in the central mineral belt.